Risk perception of COVID-19 and its related factors among centralized medical isolation groups in China - Zhang, Rui; Wang, Chengli (Frontiers in Psychology, 2023)
Objective: Medical isolation is one of the most effective measures to slow the spread of the virus when dealing with a pandemic. Millions of people in China have undergone centralized medical isolation during the COVID-19 pandemic. This study aims to assess the centralized medical isolation group's COVID-19 risk perception and to explore the influencing factors. Methods: A total of 400 participants (200 who had experienced centralized medical isolation and 200 who had not experienced) completed a questionnaire related to COVID-19 risk perceptions. The questionnaire was designed with the Cognitive-Experiential Self-Theory (CEST) and the Common Sense Model of Risk Perception (CSM). It adopted nine questions to measure risk perception in terms of Emotional feelings, Cognitive judgment, and Mental representation of unusual severity. Descriptive statistical analysis, correlation analysis, and multiple linear regression analysis were conducted with SPSS 26.0 software. Results: The mean risk perception score for the centralized medical isolation group was 30.75, with a standard deviation of 7.503, which was significantly higher than that in the non-centralized medical isolation group (risk perception score was 28.2, and the standard deviation was 7.129). The results show that risk perceptions were higher for older age, risk perceptions were higher for higher education, risk perceptions were higher for those who had received the COVID-19 vaccination, and risk perceptions were higher for those who lived in a family with children. Conclusion: Risk perception is significantly higher in centralized medical isolation groups than in non-centralized medical isolation groups. The government should draw more care to the risk perception and psychological well-being of the centralized medical isolation group and provide extra support and assistance to the elderly and those raising younger children. In dealing with future pandemics like the COVID-19 outbreak, the government should actively guide the public to properly isolate at home and cautiously implement a centralized medical isolation policy.